2001
DOI: 10.1046/j.1440-172x.2001.00257.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of coping efficacy, negative moods and post‐traumatic stress syndrome following major trauma

Abstract: The purpose of the study was to test relationships among injury appraisals, coping, social support and outcomes of coping efficacy, mood states and post-traumatic stress syndrome. A purposive sample of 152 hospitalized patients a week following major trauma was recruited from two trauma centres. The measures included the modified Ways of Coping Scale; the brief Social Support Questionnaire; the brief Profile of Mood State; the Impact of Event Scale; and selected demographic and injury related variables. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
5
37
0
Order By: Relevance
“…A study by Bolton, Glenn, Orsillo, Roemer, and Litz (2003) reported a significant negative association of selfdisclosure with PTSD symptom severity in Somalia peacekeepers. On the other hand, an avoidant coping style and wishful thinking were the best predictors for developing PTSD symptoms (Bryant & Harvey, 1995;Dougall, Ursano, Posluszny, Fullerton, & Baum, 2001;Tsay, Halstead, & McCrone, 2001).…”
Section: Coping Strategies In Daily Life As Protective and Risk Factomentioning
confidence: 97%
“…A study by Bolton, Glenn, Orsillo, Roemer, and Litz (2003) reported a significant negative association of selfdisclosure with PTSD symptom severity in Somalia peacekeepers. On the other hand, an avoidant coping style and wishful thinking were the best predictors for developing PTSD symptoms (Bryant & Harvey, 1995;Dougall, Ursano, Posluszny, Fullerton, & Baum, 2001;Tsay, Halstead, & McCrone, 2001).…”
Section: Coping Strategies In Daily Life As Protective and Risk Factomentioning
confidence: 97%
“…Coping styles employed subsequent to traumatic stressors may also play a role in either increasing risk of poor adjustment (e.g., heavy drinking or drug use to cope; Lazarus, & Folkman, 1984) or promoting resilience and decreasing an individuals' risk of developing or maintaining PTSD and depression. There has been some consensus within the literature that emotion-focused strategies are maladaptive by virtue of their generally positive association with poorer mental health outcomes, such as greater PTSD and depression symptom severity, following trauma exposure (e.g., Baschnagel, Gudmundsdottir, Hawk, & Beck, 2009;Blake, Cook, & Keane, 1992;Bryant & Harvey, 1995;Fairbank, Hansen, & Fitterling, 1991;Gil, 2005;Glass, Flory, Hankin, Kloos, & Turecki, 2009;Krause, Kaltman, Goodman, & Dutton, 2008;Nezu & Carnevale, 1987;Solomon, Mikulincer, Avitzur, 1988;Taft, Resick, Panuzio, Vogt, & Mechanic, 2007;Tiet et al, 2006;Tsay, Halstead, & McCrone, 2001). However, this association may be in part due to inadequate conceptualizations of emotion-focused coping, which have historically aggregated diverse strategies that encourage disparate ways of managing stressors, with some strategies promoting approach (e.g., seeking emotional support) and others avoidance (e.g., denial).…”
mentioning
confidence: 99%
“…Studies do demonstrate that the impact of stress generated by a situation on the response of immune system differs depending on factors like coping skill [29] and personality [17]. In contrast to other studies, the current study examined SAI scores as well as cytokine levels prior to the examination, which is associated with different degrees of anxiety, which also may have been influenced by the individual coping mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…An individual's coping skill is a modifiable factor that helps the individual to deal with stress effectively [17]. The coping skills adapted by individuals vary substantially, leading to a change in the level of stress generated [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation